Traditional malay medicinal plants - Muhamad Zakaria; Mustafa Ali Mohd (Institut Terjemahan Negara Malaysia Berhad, 2010)
Malaysia, like many other countries, is a nation that treasures its natural environment of forests, jungles and thickets. Moreover, these woodland domains also happen to be the greatest source of natural products that can be used for medicinal purposes. Since the beginning of their history, the Malay people have been using entire plants or their leaves, roots, stems, flowers or fruit as ingredients for the preparation of traditional herbal medicine. This book is an invaluable guide for people familiar with traditional medicine, as well as those who have an interest in medicinal plants. the book may also be of use to professionals such as botanists, phytochemists, doctors and pharmacologists